2021
DOI: 10.1007/s11159-021-09917-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between teachers’ teaching beliefs and their affinity for lifelong learning: The mediating role of change tendencies

Abstract: In today's era of rapid change, lifelong learning is one of the most important ways for individuals to keep up with social, cultural, economic and technological developments. This applies especially to the teaching profession, which shapes the future of societies by teaching students how to construct knowledge. The aim of the study presented here was to investigate the mediating role of change tendencies in the relationship between teachers' teaching beliefs and their affinity for lifelong learning. Using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
(114 reference statements)
0
2
0
2
Order By: Relevance
“…In a PD for the design of ODL it therefore follows that consideration of the learners needs, capabilities and environments must be recognised and their acquisition of skills, rather than knowledge, becomes paramount. Research on 228 Turkish teachers by Senturk & Bas ( 2021 ) found a positive relationship between teachers who held constructivist beliefs towards teaching and learning and their attitudes towards the benefits of educational change as represented, for example, by the introduction of ODL. This finding resulted in a call for all Turkish educational PD to be situated in both physical and pedagogical constructivist learning environments (Senturk & Bas, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a PD for the design of ODL it therefore follows that consideration of the learners needs, capabilities and environments must be recognised and their acquisition of skills, rather than knowledge, becomes paramount. Research on 228 Turkish teachers by Senturk & Bas ( 2021 ) found a positive relationship between teachers who held constructivist beliefs towards teaching and learning and their attitudes towards the benefits of educational change as represented, for example, by the introduction of ODL. This finding resulted in a call for all Turkish educational PD to be situated in both physical and pedagogical constructivist learning environments (Senturk & Bas, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Araştırmanın hayat boyu öğrenme becerilerinin yansıtılmasını etkileyen öğretmen kaynaklı unsurlarla ilgili sonuçları değerlendirildiğinde, öğretmen yeterliği ve hizmet öncesi öğretmen eğitiminin ön plana çıktığı söylenebilir. Alanyazında da öğrencilerin hayat boyu öğrenenler olarak yetiştirilmesi için en öncelikli koşulun hayat boyu öğrenen öğretmenler olduğu önemle vurgulanmaktadır (Arcagök & Şahin, 2014;Çetin & Çetin, 2017;Demirel & Yağcı, 2012;Kazu & Erten, 2016;Selvi, 2011;Şentürk & Baş, 2021;Weidinger, 2021). Araştırmaya katılan İngilizce öğretmenlerinin de hayat boyu öğrenmede öğretmen yeterliğinin öneminin farkında oldukları söylenebilir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…Helterbran (2005) ise okulların hayat boyu öğrenme sürecinde önemli görev ve sorumlulukları olduğunun altını çizerken; Selvi (2011) hayat boyu öğrenme becerilerinin kazandırılmasında okulun en uygun ortamlardan biri olduğunu vurgulamakla birlikte okulların hayat boyu öğrenme merkezi olma işlevini yeterli şekilde gerçekleştiremediğini de ifade etmektedir. Okullarda verimli bir öğrenme-öğretme sürecinin gerçekleştirilebilmesi, öğretmenlerin hayat boyu öğrenme becerilerine sahip olmasıyla yakından ilişkilidir (Selvi, 2011;Şentürk & Baş, 2021;Weidinger, 2021). Öğretmenlerin hayat boyu öğrenme becerileri ile donatılmış olması, öğrenmeyi öğrenen bireylerin ve toplumların yetiştirilmesinde önem arz etmektedir (Çiftçi vd., 2021;Demiralay & Karadeniz, 2008;Evin-Gencel, 2013;Kozikoğlu & Altunova, 2018).…”
Section: Introductionunclassified
“…Also, men with 20 or more years of experience are more likely to use active learning methods for lifelong learning than women with the same length of pedagogical experience. It is necessary to take into account the length of service and the characteristics of women and men when choosing training methods(Şentürk & Baş, 2021). Along with this, it is important to take into account the mode of training (online, offline), because the success of training for teachers with different lengths of experience and other personal characteristics also depends on it(Eynon & Malmberg, 2020).…”
mentioning
confidence: 99%